2002
DOI: 10.1002/1615-9314(20020901)25:13<789::aid-jssc789>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and applications of adsorbents containing cyclodextrins

Abstract: Synthesis and applications of adsorbents containing cyclodextrinsCyclodextrins (CDs), which possess a hydrophobic cavity, have a remarkable capacity to form inclusion complexes with various molecules through host-guest interactions. It is well known that the usefulness of CDs is due to the combination of the inclusion properties and structural features of these molecules. CDs are used extensively in separation science because CD-complexation phenomena offer a procedure of choice for separation of compounds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
198
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(203 citation statements)
references
References 322 publications
1
198
0
Order By: Relevance
“…[28][29][30][31] With the high selectivity that it provides natively, much research work has been performed with materials containing β-cyclodextrin as adsorbents, as recently reviewed by Crini. 32 Tzou and co-workers also used it to develop an SPE method for determination of digoxin and metabolites in human serum. 33 However, its usage in SPE to concentrate phenolic compounds for analysis based on its inclusion property has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] With the high selectivity that it provides natively, much research work has been performed with materials containing β-cyclodextrin as adsorbents, as recently reviewed by Crini. 32 Tzou and co-workers also used it to develop an SPE method for determination of digoxin and metabolites in human serum. 33 However, its usage in SPE to concentrate phenolic compounds for analysis based on its inclusion property has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their relatively hydrophobic cavity, CD are capable of forming inclusion complexes (IC) with variety of organic molecules and thus, CD can be effective for the removal of hazardous molecules from the surroundings by inclusion complexation (Crini and Morcellet, 2002;Olah et al, 1988;Landy et al, 2012;MorinCrini and Crini, 2013;Schofield et al, 2012). In our previous studies, we have demonstrated that CD functionalized polymeric NF can be potentially used as molecular filters for the air and water filtration by removing organic molecules from the required environment (Kayaci et al, 2013;Kayaci and Uyar, 2014;Uyar et al, 2009Uyar et al, , 2010aUyar et al, , 2010b.…”
Section: Vocs Entrapment Capability Of CD Nf and Cd Powdermentioning
confidence: 99%
“…Owing to this intriguing supramolecular mould, CD can form non-covalent host-guest inclusion complexes (IC) with a variety of molecules so they are particularly applicable in various field such as pharmaceuticals, functional foods, cosmetics, home/personal care, textiles etc (Blach et al, 2008;Flaherty et al, 2013;Harada et al, 2011;Hedges, 1998;Shao et al, 2010;Szejtli, 1998). Some molecules that CD form IC can be hazardous and polluting chemicals, so CDs are fairly useful for filtration/separation/purification areas (Olah et al, 1988;Crini and Morcellet, 2002;Landy et al, 2012;Morin-Crini and Crini, 2013;Schofield et al, 2012). For this purpose, it can be considered that, CD have also potential for the elimination of VOCs from the environment (Favier et al, 2011;Mauri-Aucejo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An aqueous alcohol, such as methanol, solution is often used as the mobile phase for CD columns in inclusion chromatography [11]. An updated review of the synthesis of CD-containing adsorbents was given by Crini and Morcellet [12]. There are primarily two types of synthetic CD-containing particles for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately the cross-linking agent is weak in its structure. Thus the polymer has a gel-like appearance with a weak mechanical strength even though the degree of cross-linking is high [12].…”
Section: Introductionmentioning
confidence: 99%